PARENTS KNOWLEDGE, EXPERIENTIAL MARKETING IN DETERMININGDECISION TO PURCHASE GADGETS FOR CHILDREN - Indriyana Prasasti; Asep Riyanna Rukhyat; Kevin Edria Nashar; Nuranisa; Artarina DA Samoedra (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Knowledge of parents about gadgets is good enough, but many parents still give gadgets to their children, even though there are some parents who experience bad events due to the dangers of gadgets used by their children. On the other hand there are currently a lot of kids who already have gadgets, which they shouldn't be old enough to have gadgets. The purpose of this study is to describe and find out how much influence the knowledge of parents, experiential marketing, in determining the decision to purchase gadgets for children. The method used is descriptive verification through a questionnaire as data collection and tested by path analysis. The results showed that parents' knowledge did not significantly influence the purchasing decisions of gadgets for children while experiential marketing had a significant effect on the purchasing decisions of gadgets for children.